Organic priority substances and microbial processes in river sediments subject to contrasting hydrological conditions - Zoppini, Annamaria; Ademollo, Nicoletta; Amalfitano, Stefano; Casella, Patrizia; Patrolecco, Luisa; Polesello, Stefano (The Science of the total environment, 2014)
Flood and drought events of higher intensity and frequency are expected to increase in arid and semi-arid regions, in which temporary rivers represent both a water resource and an aquatic ecosystem to be preserved. In this study, we explored the variation of two classes of hazardous substances (Polycyclic Aromatic Hydrocarbons and Nonylphenols) and the functioning of the microbial community in river sediments subject to hydrological fluctuations (Candelaro river basin, Italy). Overall, the concentration of pollutants (∑PAHs range 8–275ngg−1; ∑NPs range 299–4858ngg−1) suggests a moderate degree of contamination. The conditions in which the sediments were tested, flow (high/low) and no flow (wet/dry/arid), were associated to significant differences in the chemical and microbial properties. The total organic carbon contribution decreased together with the stream flow reduction, while the contribution of C-PAHs and C-NPs tended to increase. NPs were relatively more concentrated in sediments under high flow, while the more hydrophobic PAHs accumulated under low and no flow conditions. Passing from high to no flow conditions, a gradual reduction of microbial processes was observed, to reach the lowest specific bacterial carbon production rates (0.06fmolCh−1cell−1), extracellular enzyme activities, and the highest doubling time (40h) in arid sediments. In conclusion, different scenarios for the mobilization of pollutants and microbial processes can be identified under contrasting hydrological conditions: (i) the mobilization of pollutants under high flow and a relatively higher probability for biodegradation; (ii) the accumulation of pollutants during low flow and lower probability for biodegradation; (iii) the drastic reduction of pollutant concentrations under dry and arid conditions, probably independently from the microbial activity (abiotic processes). Our findings let us infer that a multiple approach has to be considered for an appropriate water resource exploitation and a more realistic prevision of the impact of pollutants in temporary waters. [Display omitted] •Hydrological conditions affected the circulation of PAHs and NPs in river sediments.•Contrasting microbial metabolic rates were associated with sediment contamination.•The proposed multiple approach identifies novel scenarios on pollutant dynamics.